Use of Information Visualization and Adaptive Hypermedia Techniques on Content Portals - Mazariolli, Rafael Vaisset; Zorzal, Ezequiel Roberto (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
This paper applies Information Visualization and Adaptive Hypermedia techniques to the development of a computational tool to adjust elements of hypermedia, based on the user profile.